Quality Matters? The Involvement of Mitochondrial Quality Control in Cardiovascular Disease - Lin, Kai-Lieh; Chen, Shang-Der; Lin, Kai-Jung; Liou, Chia-Wei; Chuang, Yao-Chung; Wang, Pei-Wen; Chuang, Jiin-Haur; Lin, Tsu-Kung (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular diseases have been one of the leading causes of death and global health problems worldwide. Multiple factors are known to affect the cardiovascular system from lifestyles, gene, underlying comorbidities and age. Requiring high workload, metabolism of the heart is largely dependent on continuous power supply via mitochondria through effective oxidative respiration. Mitochondria not only serves as cellular power plants, but are also involved in many critical cellular processes, including the generation of intracellular reactive oxygen species (ROS) and regulating cellular survival. To cope with environmental stress, mitochondrial function has been suggested to be essential during bioenergetics adaptation resulting in cardiac pathological remodeling. Thus, mitochondrial dysfunction has been advocated in various aspect of cardiovascular pathology including the response to ischemia/reperfusion (I/R) injury, hypertension (HTN) and cardiovascular complications related to type 2 diabetes mellitus (DM). Therefore, mitochondrial homeostasis through mitochondrial dynamics and quality control is pivotal in the maintenance of cardiac health. Impairment of segregation of damaged components and degradation of unhealthy mitochondria through autophagic mechanism may play a crucial role in the pathogenesis of various cardiac disorders. This article provides in-depth understanding of current literatures regarding mitochondrial remodeling and dynamics in cardiovascular diseases.